Informalisation and the social relations of production: Insights from urban Karnataka, 1990––2005. (1st July 2011) - ,
Abstract : This article draws upon evidence from urban centres in the Indian state of Karnataka in order to explore the impact of informalisation on labour. It is argued that informalisation is best understood by outlining specific changes to the social relations of production. This issue is approached by comparing and contrasting Marxist claims about class formation with findings from an analysis of Economic Census data. The Economic Census has recorded a rise in waged labour in informal enterprises in urban Karnataka and a rise in sole trading in own-account establishments. It concludes by pointing towards the need for further research into the growing employment of ''informal workers'' in the formal economy.